Aspergillus fumigatus ctf1–a novel zinc finger transcription factor involved in azole resistance - Xiao Gong; Heng Zhang; Wenxu Cheng; Zhangxuan He; Tianyan Ma; Tian Chen; Yi Sun (Mycology)
Elucidating the mechanisms underlying antifungal resistance in Aspergillus fumigatus, discovering new antifungal targets, and developing drugs to inhibit resistance are the key approaches to treating A. fumigatus infections. Here, we investigated the function of ctf1 (AFUA_1G03800), a gene encoding a C6 transcription factor. Homologous recombination replacement technology was employed to construct ctf1-knockout and revertant strains. Fungal morphological observations revealed that the growth of the knockout strain was slower, showing fewer conidia. The minimum inhibitory concentration of triazoles was determined by performing the E-test and by using the micro-liquid-based dilution method. The results indicated that ctf1 deletion decreased the susceptibility of A. fumigatus to voriconazole by 2-fold. The decreased antifungal sensitivity of Δctf1 can be attributed to the increased ergosterol content and the overexpression of mdr1, mdr2, and mdr4. Thus, our results on the function of ctf1 contribute to the elucidation of the mechanisms underlying A. fumigatus resistance and the factors associated with A. fumigatus virulence.